Cuka Wain Dari Perspektif Islam: Analisis Fatwa Malaysia Dan Indonesia - Pauzi, Norhidayah; Man, Saadan (Jurnal Fiqh, 2016)
Wine vinegar is often used in the preparation of food in most hotels and restaurants. Issues in the usage of wine vinegar arise due to the formation of liquor in its production process. Malaysia and Indonesia have recpectively issued different fatwa on this issue, causing confusion to industry players and consumers. This research discusses the ruling (hukm) of the usage of wine vinegar and attempts at analyzing the differences in the fatwas issued by both countries. To achieve the objectives of this study, the library research and field studies methodologies were undertaken. This study finds that Malaysia is in the view that wine vinegar is permissible if the substance changed naturally from wine to vinegar. However, the fatwa holds that wine vinegar is prohibited if it is produced by using external substance. Malaysia is predominantly attached to the ShafiÂ’i school of thought and thus put the stringent conditions in accepting the concept of istihalah. In contrast to its counterparty, Indonesia is in the view that vinegars produced naturally from wine or through the addition of external substance are both permissible. In this case, Indonesia adopts the Hanafi and Maliki schools of thought and seems to use the concept of istihalah consistently in its halal food standards.